Chinese Ethnic Identity Politics in Singkawang City Election - Azizah Larasati; Hildawati; Roma Tressa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The political identity of ethnic Chinese has existed since the Dutch colonial rule through Chinese organizations that aimed to abolish discriminatory treatment of Chinese people. Ethnic Chinese take advantage of democratic freedom in various political events by forming organizations such as political parties. The involvement of ethnic Chinese in politics is inseparable from the history, groups and communities of ethnic Chinese continue to show their existence in multiethnicity in Singkawang City. In this study, the author uses a qualitative analysis research method that is descriptive. Data collection using interviews and documentation. The results of the study show that the Mayor of Singkawang City in 2017 was the first female ethnic Chinese mayor in the history of China and the City of Singkawang. Reviewing back in 2017 and the 2024 election, the Chinese won by the same actor. The use of the election factor and the use of ethnic Chinese identity politics in Singkawang City are very different from the previous year. The most widely used and very influential power factor to determine victory. The use of ethnic Chinese identity politics does not seem dominant, but the existence of actors in each couple.